Antibiogram Typing of Urinary Pathogens Isolated from Patients Visiting Tertiary Care Hospital, Dharan, Sunsari, Nepal - Chaudhary, Kumu; Dongol, Pranita; Khanal, Hemanta (Himalayan Journal of Science and Technology, 2017)
Abstract available with the full text PDF.